Serum Ferritin Predicts Neither Organ Dysfunction Nor Mortality in Pediatric Sepsis Due to Tropical Infections - Williams, Vijai; Menon, Nisha; Bhatia, Prateek; Biswal, Manisha; Sreedharanunni, Sreejesh; Rawat, Amit; Jayashree, Muralidharan; Nallasamy, Karthi (Frontiers in Pediatrics, 2020)
Objective: To evaluate serial ferritin levels measured in the initial 72 hours of admission as a biomarker for new and progressive multiorgan dysfunction syndrome(NPMODS) and mortality (unfavorable outcomes) in critically ill children with sepsis due to tropical infections. Material and methods: In this prospective observational study from a tertiary care teaching hospital in India, children 3 month to 12 years with a diagnosis of acute febrile illness and any two features suggesting tropical infections [cytopenia (platelet count<1,00,000/cu.mm, total leucocyte count<4000/cu.mm), hepatomegaly and/or splenomegaly, lymphadenopathy, systemic signs (rash, edema), respiratory distress and encephalopathy not accounted by localized infection] were eligible for inclusion. Children with known or suspected disorder of iron metabolism were excluded. Primary outcome was to determine the association of serial ferritin levels with mortality and NPMODS. Secondary outcomes included estimation of the prevalence of hyperferritinemia and comparison of risk prediction scores with serial ferritin measurement in predicting unfavorable outcomes. Measurements and main results: In the 202 children enrolled, diagnosis could be established in 133(65.8%) children. Scrub typhus and dengue were the most common infections. Median(IQR) ferritin measured at admission(n=183) and on day 3(n=120) of hospital stay were 798(378,3205) µg/L and 429(213,680) µg/L respectively. Majority[n=180,89.1%] had MODS at admission defined as per International pediatric sepsis consensus conference. NPMODS occurred in 47(23.3%) children of whom 37(18.3%) died. Children with <3 organ dysfunctions had lower mortality. Neither admission ferritin values nor the percentage change over 72 hours was different between children with favorable and unfavorable outcomes. Pediatric Risk of Mortality (PRISM-III) and daily Pediatric Logistic Organ Dysfunction score (dPELOD2 score) were significantly different in those with unfavorable outcomes. Admission ferritin levels and percentage change in 72 hours had poor discriminatory power for mortality with AUC of 0.53(0.53,0.67) and 0.50(0.50,0.64) respectively. dPELOD2 had the best discriminatory power for mortality with AUC of 0.89(0.89,0.95). Conclusions: Serial ferritin estimation predicted neither organ dysfunction nor mortality in pediatric sepsis with tropical infections. dPELOD-2 and PRISM-III predicted unfavorable outcomes better than ferritin. The current diagnostic criteria for MODS overestimated organ dysfunctions in tropical infections and hence may need modification with further validation in this epidemiological cohort.